Comparative study on non descent vaginal hysterectomy verses abdominal hysterectomy for benign uterine conditions - Kshma Chandrakar; Neelam Singh; Surekha Charla (International Journal of Medical Research and Review, 2016)
Objectives: To determine superiority, safety and effectiveness of vaginal over abdominal route of hysterectomy and to show that vaginal hysterectomy requires shorter duration of surgery, less blood loss, early post operative recovery with early ambulation of the patient, less operative complication & less duration of hospital stay compared to total abdominal hysterectomy.Methodology: A prospective comparative study conducted among 150 women undergoing hysterectomy for benign uterine condition .Those undergoing non descent vaginal hysterectomy were compared with those undergoing total abdominal hysterectomy.Results: When we compared NDVH with TAH it was found that it takes less time [86.32±9.74] min ,with lesser blood loss [171.32±36.58]ml as compared to[106.41±15.72]min and [210.45±70.45]ml in abdominal hysterectomy. The pain scores and hospital stay is also favorable in vaginal route.Conclusion: From our study we conclude that a scar less surgery in the form of NDVH should be preferred by all surgeons as the primary route of perform hysterectomy. Previously considered contraindications for NDVH have now been ruled out.